2021
DOI: 10.3390/en14144267
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Computation of Network Indicators for Electricity Market Bidding Zones Configuration Considering Explicit N-1 Security Constraints

Abstract: In this paper an optimization problem designed to calculate electric grid specific indicators to be used within model-based methodologies for the definition of alternative electricity market bidding zone configurations is designed. The approach integrates within the framework of a bidding zone review process aligned to the specifications of the Commission Regulation (EU) 2015/1222 (CACM) and Regulation (EU) 2019/943 of the European Parliament and of the Council (CEP). The calculated solution of the optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The calculation of the LMP and PTDF, however, must be carried out by running OPF on real grid portion, by including all the grid constraints. In Bovo et al [21], the authors suggested a novel OPF formulation including explicitly N-1 security criteria. All contingency-related constraints were introduced in a compact form, so that the application to large-scale test results suitable.…”
Section: Simulation Of Power Systems and Marketsmentioning
confidence: 99%
“…The calculation of the LMP and PTDF, however, must be carried out by running OPF on real grid portion, by including all the grid constraints. In Bovo et al [21], the authors suggested a novel OPF formulation including explicitly N-1 security criteria. All contingency-related constraints were introduced in a compact form, so that the application to large-scale test results suitable.…”
Section: Simulation Of Power Systems and Marketsmentioning
confidence: 99%